2008
DOI: 10.1074/jbc.m705747200
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine- and Epinephrine-induced Distinct β2-Adrenoceptor Signaling Is Dictated by GRK2 Phosphorylation in Cardiomyocytes

Abstract: Agonist-dependent activation of G protein-coupled receptors induces diversified receptor cellular and signaling properties. Norepinephrine (NE) and epinephrine (Epi) are two endogenous ligands that activate adrenoceptor (AR) signals in a variety of physiological stress responses in animals. Here we use cardiomyocyte contraction rate response to analyze the endogenous ␤ 2 AR signaling induced by Epi or NE in cardiac tissue. The Epi-activated ␤ 2 AR induced a rapid contraction rate increase that peaked at 4 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 39 publications
(42 reference statements)
2
41
1
Order By: Relevance
“…3A). However, stimulation with 10 M Iso induced a time-dependent clustering of ␤ 2 ARs in the cells, similar to those reported previously (8), which is a characteristic of receptor internalization (Fig. 3A).…”
Section: Agonist Stimulation Induces a Dose-dependent Distinct Pka Ansupporting
confidence: 77%
See 2 more Smart Citations
“…3A). However, stimulation with 10 M Iso induced a time-dependent clustering of ␤ 2 ARs in the cells, similar to those reported previously (8), which is a characteristic of receptor internalization (Fig. 3A).…”
Section: Agonist Stimulation Induces a Dose-dependent Distinct Pka Ansupporting
confidence: 77%
“…At both low and high concentrations of agonist, the activated ␤ 2 ARs undergo the PKA-mediated phosphorylation. In comparison, only high concentrations of agonist induce the GRK-mediated phosphorylation of the ␤ 2 ARs for subsequent internalization, which is also necessary for sufficient receptor coupling to G i proteins (8,9). Our studies link together various components of the ␤ 2 AR, including receptor phosphorylation, receptor trafficking, and differential receptor/G protein coupling in cardiac cells, which may allow the activation of the ␤ 2 AR signaling pathway to function as either a stimulatory or protective mechanism for cardiac cells under different levels of stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different release mechanisms and functional roles of the two endogenous agonists raise the possibility that they might also display distinct mechanisms of receptor activation and signaling. Such different activities between epinephrine and norepinephrine have recently been reported for cardiomyocyte ␤ 2 AR, where norepinephrine was observed to induce slower GRK2-mediated phosphorylation, receptor internalization and recycling, and no coupling to G i , when compared with epinephrine (18).…”
mentioning
confidence: 99%
“…We combined this observation of apical-basal βAR and basal-apical neural gradients with a second interesting pharmacological observation. Epinephrine at low and medium doses is a positive inotrope, but at the highest doses it becomes a negative inotrope via the β2AR, by activating a switch from the stimulatory Gs to the cardioinhibitory Gi pathway in a process known as stimulus trafficking (Figure 3), 21,22 which could explain the negative inotropy observed in the apical myocardium after exposure to very high levels of circulating epinephrine. We developed a rat TTS model and demonstrated that an intravenous bolus of high-dose epinephrine triggered acute apical hypokinesia, with preserved basal contractility, recapitulating the clinical features of TTS.…”
Section: Wasted Time and Now Doth Time Waste Me -William Shakespeamentioning
confidence: 99%